2022
DOI: 10.1155/2022/1625290
|View full text |Cite
|
Sign up to set email alerts
|

Vericiguat Modulates Osteoclast Differentiation and Bone Resorption via a Balance between VASP and NF-κB Pathways

Abstract: Bone homeostasis has been a dynamic equilibrium between osteoclasts (OCs) and osteoblasts (OBs). However, excessive activation of OCs could disturb the bone homeostasis. As a result, effective medical interventions for patients are greatly demanding. NO/guanylate cyclase (GC)/cGMP signaling cascade has been previously reported to regulate bone metabolism, and GC plays a significantly critical role. Vericiguat, as a novel oral soluble guanylate cyclase (sGC) stimulator, has been firstly reported in 2020 to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…39 While the primary focus of research on VIT has been on its cardiovascular benefits, some studies have also observed its effects on bone metabolism. 20 Preliminary findings suggest that VIT may have both positive impacts on bone health. 18,20 On one hand, VIT has been shown to promote osteoblast differentiation and activity, which are essential for bone formation.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…39 While the primary focus of research on VIT has been on its cardiovascular benefits, some studies have also observed its effects on bone metabolism. 20 Preliminary findings suggest that VIT may have both positive impacts on bone health. 18,20 On one hand, VIT has been shown to promote osteoblast differentiation and activity, which are essential for bone formation.…”
Section: Discussionmentioning
confidence: 90%
“…20 Preliminary findings suggest that VIT may have both positive impacts on bone health. 18,20 On one hand, VIT has been shown to promote osteoblast differentiation and activity, which are essential for bone formation. 18 By enhancing the levels of cGMP, VIT may stimulate the growth and function of osteoblasts, ultimately contributing to an increase in bone mineral density (BMD).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These effects were not seen in adult animals. In these circumstances, the continuation of experimental studies is necessary to solve this problem before starting clinical trials in children [ 50 ].…”
Section: Pediatric Populationmentioning
confidence: 99%
“…Bone repair and regeneration are well-known to be a dynamic and balanced process involving cells such as MSCs, inflammatory cells, osteoblasts, and osteoclasts [22]. BMSCs are commonly used as seed cells in bone tissue engineering because of their ability to self-renew and differentiate multi-directionally [23].…”
Section: Introductionmentioning
confidence: 99%